Controlling banker's bonuses: Efficient regulation or politics of envy? - Kent Matthews; Owen Matthews (Cardiff University, Cardiff Business School, 2009)
The positive relationship between bank CEO compensation and risk taking is a well established empirical fact. The global banking crisis has resulted in a chorus of demands to control banker's bonuses and thereby curtail their risk taking activities in the hope that the world can avoid a repeat in the future. However, the positive relationship is not a causative one. In this paper we argue that the cushioning of banks downside risks provide the incentive for banks to take excessive risk and design compensation packages to deliver high returns. Macro-prudential regulation will have a better chance of curbing excess risk taking than controlling banker's compensation.
Keywords: G21; G28; 330; banker's bonus; risk taking; too-big-to-fail; macro-prudential regulation; Bank; Führungskräfte; Anreizvertrag; Bankenaufsicht; Finanzmarktkrise; Welt